Work environment and perception of institutional image - Bravo Herrera, Rolando Ivan (2021)
This research provides a scientific treatment that allowed knowing how the work environment is related to the perception of the institutional image of an educational institution of Villa María del Triunfo district. It was developed within the quantitive approach, based on the correlational-substantive and cross-sectional design. The census sample included 40 people, between administrative and teaching staff (primary and secondary level) of the mentioned institution. The surveys allowed verifying that there is a relationship between the variables. It was concluded that there is a significant relationship between work environment and institutional image. With these results it will be possible to execute plans that allow a working environment to be strengthened and thus not have low levels of perception in the institutional image, either of public or private entities.